DA’WAH IN THE FACE OF CHRISTIAN PERSECUTION: THE HISTORICAL DEVELOPMENT OF THE MUSLIM STUDENTS’ SOCIETY OF NIGERIA (MSSN) - Rufai, Saheed Ahmad (Journal of Al-Tamaddun, 2011)
The purpose of this paper is to articulate the preliminary attitudes of the Nigerian Muslim youths to persecution through education. This research traces the origins of the Muslim Students’ Society of Nigeria (MSSN) through which they bailed themselves out of the unpalatable experience. This paper draws a picture of the religious climate of the country during the early days of the emergence of the Society and enumerates the various activities and programs through which the Society pursued its aims and objectives. It also pays attention to the main features of various developmental stages through which the Society passed. Given the hitherto dearth of reliable and sophisticated scholarship on the subject, the paper relies more, and not solely, on oral information formally collected from some of the credible individuals who were both eye-witnesses and dramatic personae in the persecution that stimulated the formation of the Muslim Students’ Society of Nigeria. The paper also employs a historical method of analysis and restricts itself to the first three decades of the Society’s emergence. It concludes that the specific aims and objectives of the Society were only achieved and managed successfully within the stipulated period.